72 Normoxic perfusion strategy in cyanotic heart disease results in a significant increase in oxygen extraction ratio. (15th December 2021) - Cross, Nigel; Wheeler, Kyrie; Crook, Richard; Issitt, Richard W
Abstract : Background: Hyper-oxygenation of cyanotic patients during the early phase of cardiopulmonary bypass can lead to significant myocardial damage. To mitigate this, the partial pressure of oxygen in arterial blood (PaO2) can be matched to the pre-operative patient levels and slowly corrected to more normal values over the first 20–30 minutes of bypass. However, it is yet to be demonstrated how this relates to oxygen extraction which is normally 25% of the delivered oxygen level. Methods: We treated a patient undergoing type 1 truncus arteriosus repair at two weeks old with an oxygen fraction of 21% to replicate a normoxic mix during cardiopulmonary bypass to assess the adequacy of oxygen delivery and extraction. Data were extracted from the patient's electronic patient record via SQL query. Data collected included demographics, intraoperative measurements, blood gas analysis and postoperative outcomes. Results: The patient was cyanotic pre-operatively with a PaO2 of ~4kPa. At the start of bypass, the PaO2 was 10kPa, and gradually increased to 17kPa as the patient was cooled to 22°C during 20 minutes prior to aortic cross clamping. The base deficit remained between -1 and 1mmol/L throughout, with a minimum SvO2 of 85%. The mean oxygen delivered was 79.7 ml/min and mean oxygen extraction of 3.6 ml/min, representing an average oxygen extraction of 4%. The patient had a successful repair and no adverse events during the post-surgical period. Conclusions: The data demonstrate the adequacy of oxygen delivery with no evidence of a shortfall in supply even at low delivered PaO2 which is known to reduce injury to the myocardium of cyanotic paediatric patients. Furthermore, the level of oxygen extracted during the procedure was 21% lower than normally observed. Further work is needed to elucidate the role that sedation and anaesthesia play from cyanotic pathophysiology and whether similar effects are seen in acyanotic heart disease.